2006
DOI: 10.1111/j.1444-2906.2006.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro methyl farnesoate secretion by mandibular organs isolated from different molt and reproductive stages of the crab Oziotelphusa senex senex

Abstract: Considerable evidences indicate that mandibular organ (MO) of crustaceans secrete terpenoid hormone (methyl farnesoate [MF]), which regulates molting and reproduction. In the freshwater south Indian rice field crab Oziotelphusa senex senex, MO isolated during premolt and vitellogenesis, secreted greater amounts of MF, which indicates that the regulation of the crustacean molt and reproduction is complex and also involves MF, besides steroid (ecdysteroid) and peptide (sinus gland peptide) hormones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 32 publications
1
34
0
2
Order By: Relevance
“…This observation correlates with the high TIs of red-phase animals, consistent with the idea that MF stimulates testicular growth either directly or indirectly in crustaceans (Kalavathy et al, 1999;Nagaraju et al, 2003;Nagaraju et al, 2006;Reddy et al, 2004). These observations are similar to previous studies in the spider crab (Libinia emarginata), which demonstrated a correlation between the reproductive status of males and MF synthesis by the mandibular organ (MO) and hemolymph levels of MF (Sagi et al, 1993;Sagi et al, 1994).…”
Section: Discussionsupporting
confidence: 81%
“…This observation correlates with the high TIs of red-phase animals, consistent with the idea that MF stimulates testicular growth either directly or indirectly in crustaceans (Kalavathy et al, 1999;Nagaraju et al, 2003;Nagaraju et al, 2006;Reddy et al, 2004). These observations are similar to previous studies in the spider crab (Libinia emarginata), which demonstrated a correlation between the reproductive status of males and MF synthesis by the mandibular organ (MO) and hemolymph levels of MF (Sagi et al, 1993;Sagi et al, 1994).…”
Section: Discussionsupporting
confidence: 81%
“…In vitro, MF production has been associated with ovarian development in C. maenas, L. emarginata and U. pugilator Laufer et al, 1987). Similarly, in vivo MF levels have been correlated with ovarian maturation and molting in the crab O. senex senex (Nagaraju et al, 2006). Administration of MF increased the Vg titer in hemolymph of ESA spider crab (Vogel and Borst, 1989).…”
Section: Mfmentioning
confidence: 99%
“…The physiological function for MF was enigmatic in crustaceans until its analogy with the gonadotropic hormone JH III from insects was established ); a recent report suggests MF to be the precursor for insect JH (Teal et al 2014). In vitro and in vivo experiments have demonstrated an association between MF production and ovarian development in C. maenas, Libinia emarginata, and Procambarus clarkii , Laufer et al 1998, Nagaraju et al 2006, Nagaraju 2011. Recent studies on the biosynthesis and release of farnesoic acid and MF within the gland (MO) revealed that the rates of biosynthesis of FA and MF were stagedependent, with maximal production (with a threefold increase) occurring during secondary vitellogenesis, i.e., stages 4 and 5 in Homarus americanus (Tiu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A major limitation in investigating the exact role of MO has been its anatomical location which has made its surgical removal difficult. Therefore, it has not been possible to perform the 'classical' ablation-replacement experiments to probe into the MO function, unlike the situation in the corpora allata of insects (Nagaraju et al 2006). …”
Section: Introductionmentioning
confidence: 99%